Alternative Assessment of Urban Flood Management Using Eco Drainage approach (Case Study: The area of the Terminal Payung Sekaki ) - Saputra, Ricko Adi; Suprayogi, Imam; Sasmita, Aryo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The area of the Terminal payung sekaki in the future directed by function area of Commerce (business), the ground transportation center and the main entrance gate Pekanbaru city by land for the constellation of the most prestigious regional and city of Pekanbaru in particular. Land conversion happens on the open land into developed regions an impact on the improvement of storm water runoff and impairment infiltration or water storage amount that goes into the ground. Eco drainage is drainage infrastructure of urban areas where rainfall runoff is not directly channeled water receiver but accommodated in the retention pond to provide sufficient time for the water to seep into the ground. Retention pond is designed not only as flood control but also as a place of recreation for the park to be combined with increasing the area of green open space and improve the esthetic value of theenvironment. The completion of this study using EPA SWMM 5.0 assistance program to analyze the suitability of the drainage capacities to cope with the flood problem. The results showed that the problem of flooding due to the capacity of the existing channel with a dimension of 1x1 m not in accordance with the conditions of rain and runoff into drainage capacities with a value of 1.0 or 100% has been filled with runoff that goes into the drainage. Simulation repairs done by using the channel dimensions 2x2 m still not able to cope with the recent flooding. The capacity of the existing line with the percentage Impervius undeveloped land with a value of 85%, 60% and 2% can be maximized by the addition of the retention pond with an area of 2 hectares and a depth of 2 m as well as changes in the dimensions of the channel just upstream (3x3m) and downstream (2x2m) into alternative solutions to problems ofurban flooding in the region. The capacity of drainage channels and retention ponds planned until the 20 years in the future development of the city of pekanbaru RTRW according to changes in the percentages of land be impervius 95% still holds a runoff into drainage channels so that the problem of flooding in the area of AKAP Subdistrict payung sekali can be resolvedKeyword : Flooding, Eco drainage, Retention Ponds , EPA SWMM 5,0